Myopia Progression in Adults: A Retrospective Analysis - Khan, Hashim Ali; Naduvilath, Thomas; Tahhan, Nina; Sankaridurg, Padmaja R (Optometry and vision science, 2023)
Studies on adult myopia progression are limited. This retrospective analysis of a large data set of young adult myopes characterizes myopia progression during adulthood. This study aimed to determine the mean annual progression of myopia and to estimate the proportion of progressors in adult myopes. Longitudinal, noncycloplegic subjective refraction data for young adult myopes (spherical equivalent refractive error, -0.5 D or more), age ranging from 18 to 30 years, were retrospectively analyzed. The mean annual progression, as well as the proportion of progressors (at least -0.50 D shift between visits and annualized progression of -0.25 D or more), was estimated. A total of 354 myopes (230 females [64.7%]), with a mean (standard deviation) age of 22.2 (3.8) years, were considered. The mean (standard deviation) annualized progression was -0.10 (0.21), -0.08 (0.2), and -0.04 (0.21) D in the 18- to 21-year, 22- to 26-year, and 27- to 30-year age groups, respectively ( P = .003). The difference between 18- to 21- and 27- to 30-year age groups was significant ( P = .05), whereas all other pairwise comparisons were not significant. The proportion (95% confidence interval) of progressors in the 18- to 21-, >21- to 26-, and >26- to 30-year age groups was 18.3% (14.9 to 21.7%), 10.9% (7.1 to 14.7%), and 8.8% (4.4 to 13.1%), respectively. The proportion of progressors working or studying in a higher learning/academic environment was 16.2% with an odds ratio (95% confidence interval) for progression of 2.07 (1.15 to 3.74) compared with those in nonacademic environments ( P = .02), with no significant effect of sex or ethnicity. This study is consistent with other studies on myopia in young adults, which show that myopia does not progress by substantial amounts throughout the adult years, particularly after the age of 21 years. Although future studies may be challenged by the small rates of change and the small proportion of progressors, further research is needed to understand the implications of adult myopia progression on clinical management.